Current problems of health protection of the working population in Russia - N. G. Petrova; S. E. Teptin; S. G. Pogosyan (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The authors studied the extent of chronic diseses and of pathological conditions in the working people in on district of the Leningrad region using the data of prophylactic examination. The analysis showed that practically all people (90.4 % of the examined people) had chronic diseases: 26.3 % of the people had one pathology, 29.6 % had two diseases, and 34.5 % of the people had three and more pathologies. The women were more vulnarable than the men to three and more pathologies (40.2 % and 22.2 % of the cases respectively. The data obtained should be the basis for planning of the scope of preventive, curative and diagnostic measures for the working population.